Collaborative Governance Dalam Pengelolaan Daerah Aliran Sungai Cidanau Provinsi Banten - Julianes Cadith; Wulandari, Liani (Sawala : Jurnal Administrasi Negara, 2024)
This research aims to identify the collaborative governance conducted by the Cidanau River Basin Communication Forum (FKDC) in the management of the Cidanau River Basin. The goal is to obtain an overview of the collaboration process based on Ansell & Gash’s (2008) theory, which consists of four main variables: 1) Starting Conditions, 2) Institutional Design, 3) Facilitative Leadership, and 4) Collaboration Process. This study employs a qualitative method with a descriptive approach, using data collection methods such as observation, interviews, documentation review, and literature study. Data validity is checked through triangulation and member checks. The results of the study indicate that the collaborative governance involving the Banten Provincial Government, private sector, community, NGOs, academics, and media is functioning reasonably well but not yet optimal. This is evident from ongoing issues with face-to-face dialogue, such as the lack of government participation during forum meetings. Additionally, the problems in the Cidanau area that prompted this collaboration have not been fully resolved. It is hoped that FKDC will improve organizational management by establishing written rules that all stakeholders must adhere to. Furthermore, FKDC is also expected to involve more experts in the field to address the Cidanau River Basin issues more effectively.